O Mere des amours, Ciprene - Lasso, Orlando di,Sandberger, Adolf (Breitkopf and Härtel, 1927)
O mère des amours Ciprine – Tu sais o gentille – Or cesse doncques
For chorus (SATB), unaccompanied. - Full Score
Keywords: Polyphonic chansons